Muslim values and market value: a sociological perspective. (4th March 2014) - Dean, Jason
Abstract : Purpose: – The paper aims to study the consequences of the development of Islamic marketing on the social construction of Muslim religious identities. Design/methodology/approach: – The paper uses Max Weber's ideal-type methodology to analyze actors and strategies in Islamic marketing, as represented by their self-presentation on French-, English- and Arabic-language web sites. Findings: – First, the paper argues that by conflating values and preferences, rational choice theory fails to recognize an essential function of values, which govern the relationship between the personal and the social. Second, it describes the emergence of brand markets within traditional Muslim commodity economies. Third, it uses these distinctions, between the personal and the social and between commodity and brand economies, to construct four ideal types of Muslim economic actors: "collectivists", "differentialists", "integrationists", and "entrepreneurs". Research limitations/implications: – The choice of web sites to survey Muslim economic and religious actors favors producers over consumers, religious specialists over laypeople. Future research should include protocols designed to test ways in which Muslims negotiate the conflicting demands of religion, society and economics in their daily lives. Originality/value: – In contradistinction to studies that emphasize the influence of Muslim consumer demand on the development of goods and services, this paper shows that economic conditions, notably globalization and market segmentation, affect the way Muslims construct their religious identities.